Alteração na expressão das enzimas 3-HSD e aromatase nos testículos de ratos adultos submetidos a exposição crônica ao herbicida atrazina, seguida de um período de recuperação - Elisângela Martins dos Santos (2013)
Atrazine is the active compound of herbicides, considered as a potent endocrine disruptor, causing various reproductive disorders in males. The mechanism of action of atrazine is not completely determined, but in vitro studies have demonstrated that atrazine induces the RNAm expression and activity of aromatase, the enzyme that converts androgens to estrogens. In addition, was demonstrated in vivo the negative impact of atrazine in the expression of the steroidogenic enzyme 3-HSD in the testis. In spite of the seriousness, it is not known whether these effects of atrazine on male reproduction are permanent or transient, the main goal of the present study. Additionally, we intend to evaluate, in an in vivo model, atrazine was also cause changes in the protein levels of aromatase. Were used male Wistar rats, adult, which were treated with atrazine at the dosage of 200mg/Kg for 7, 15 or 40 days. Part of the animals treated for 40 days were subjected to a period of 75 days for recovery from exposure to the herbicide. The results showed changes were observed in the morphology and reduced 3-HSD from 7 days of exposure, while changes in the expression of aromatase occurred later. Changes included transient increase in testicular weight, testicular atrophy and luminal dilation. Testicular atrophy and the reduction of 3-HSD was more marked after 75 days of cessation of exposure to the herbicide, suggesting that the effects of atrazine are extended in the testes and irreversible. In short, this study adds important information on the adverse effects of this herbicide as a potent endocrine disrupter.